Ficciones y límites La diversidad funcional en las artes escénicas, la literatura, el cine y el arte sonoro - Gómez García, Alba; Navarro Juan, David; Velloso Álvarez, Javier (Images of Disability. Literature, Scenic, Visual, and Virtual Arts / Imágenes de la diversidad funcional. Literatura, artes escénicas, visuales y virtuales, 2021)
Our understanding of reality and our relationship with it are often conditioned by the influence of the images that cultural systems produce and circulate. The discourses that contribute to shaping a socially accepted idea about functional diversity are many and varied, but there is no doubt about the definitive role that the arts also play. This volume brings together a series of theoretical and practical approaches that analyze the uses and nature of some contemporary fictions, and offers a new look at the risks and challenges, as well as the aesthetic and political possibilities and limits, which the representation of functional diversity in the performing and audiovisual arts, literature and sound art.